2006
DOI: 10.1007/s10350-006-0692-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Recurrence in Patients with Crohn's Disease Under Nutritional Therapy

Abstract: Among patients with Crohn's disease under maintenance enteral nutrition, the risk of recurrence differs according to the disease type and the site of involvement. The maintenance treatment by enteral nutrition alone seems insufficient for patients with penetrating type or with colonic involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…Esaki et al [52] also noted that remission can be prolonged by supplementary enteral nutrition. They conducted a retrospective, single centre study on an adult cohort of patients with CD.…”
Section: Een and Relapsementioning
confidence: 99%
“…Esaki et al [52] also noted that remission can be prolonged by supplementary enteral nutrition. They conducted a retrospective, single centre study on an adult cohort of patients with CD.…”
Section: Een and Relapsementioning
confidence: 99%
“…A retrospective study of 145 patients in remission, with twothirds receiving maintenance EN, identified penetrating CD (RR 3.89; 95% CI 1.58-9.62), colonic involvement (RR 3.10; 95% CI 1.39-6.90) and previous history of surgery (RR 2.48; 95% CI 1.16-5.33) to be factors that predicted recurrence [Esaki et al 2006]. Recurrence rates were high (42/98 EN group versus 29/47 normal diet; p = 0.047), and it is difficult to assess the applicability of these data since remission was induced with PN and the only other therapy used was 5-aminosalicylic acid drugs.…”
Section: Maintenance Of Remission: Enteral Nutritionmentioning
confidence: 99%
“…Esaki et al [31] have demonstrated in a trial of 145 patients with CD (mostly induced into remission with TPN) that, under maintenance with elemental/polymeric nutrition, the risk of recurrence was lower in those with small bowel rather than large bowel involvement.…”
Section: Enteral Feedingmentioning
confidence: 97%